ANALISIS NILAI EKONOMI WISATA KEBUN KINA BUKIT UNGGUL KABUPATEN BANDUNG - Listiana Widya Wanti; Yusman Syaukat; Bambang Juanda (Departemen Ekonomi Sumberdaya dan Lingkungan, Fakultas Ekonomi dan Manajemen, Institut Pertanian Bogor, 2014)
For the past several decades, tourism sector is continuously growing and become one of the fastest growing economic sectors in the world. Indonesia also shows an increasing trend on tourism. PT Perkebunan Nusantara VIII (PT PN VIII), a state-owned plantation enterprise, is trying to develop agrotourism potentials in each of their plantation unit. Bukit Unggul plantation is one of many plantations owned by PT PN VIII, which has been developing Bukit Unggul Quinine Tourism since 2009. As a tourism site, Bukit Unggul has the intangible benefits and characteristics of public goods, which are non-rivalry, non-excludability, and congestible. The main characteristic of public goods is the absence of market and pricing mechanism. The objectives of this study are to identity factors that influence demand (visiting frequency) and to estimate the economic value of Bukit Unggul Plantation Tourism. This study used travel cost method in its economic analysis. The result of tourism demand analysis shows that demand (visiting frequency) is positively influenced by tourists’ monthly income and the time needed to get information about the tourism site, and it is negatively influenced by the distance to the site. Consumer’s surplus per visit in this tourism demand model is IDR 166,700. The economic value of Bukit Unggul Quinine Plantation Tourism Site is IDR 1,108,054,900 per year.